2021
DOI: 10.35864/evmd.906990
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen isolation and antibiogram analysis in dairy cows with clinical mastitis in Adana region, Turkey

Abstract: The goal of this study was to investigate pathogen types found in milk samples from cows with clinical mastitis, as well as the sensitivity of isolated bacteria to different antibiotics. The study was carried out on 103 milk samples collected from dairy cows with clinical mastitis. Microbiological isolation and identification were performed to identify gram negative and gram positive bacteria, Mycoplasma bovis and fungi. Then, bacteria isolated from infected milks were subjected to antibiogram, using 27 antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Holstein cows (6 years of age) from a commercial farm (Wuzhong City, Ningxia Hui Autonomous Region, China) were evaluated for clinical mastitis. The udder examination was performed according to the criteria for veterinary clinical diagnosis, including redness, temperature, swelling and pain [ 20 ]. Milk samples (20–25 mL) from the Holstein cows were collected for somatic cell count (SCC) as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Holstein cows (6 years of age) from a commercial farm (Wuzhong City, Ningxia Hui Autonomous Region, China) were evaluated for clinical mastitis. The udder examination was performed according to the criteria for veterinary clinical diagnosis, including redness, temperature, swelling and pain [ 20 ]. Milk samples (20–25 mL) from the Holstein cows were collected for somatic cell count (SCC) as described previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the cows in both groups were between about 3.5-5 years old, and did not have any clinical problems at the time of study. The previous health and disease information of the cows was obtained from the records, and metritis was characterized as previously described, taking into account findings such as fever, and fetid watery red-brown uterine discharge (Genís et al, 2018;Kurt et al, 2019). In addition, animals in two groups were included in the study according to the results of microbiological examination.…”
Section: Animals and Groupsmentioning
confidence: 99%
“…Uterine infections have an incidence of up to 50% in the postpartum period in dairy cows (Manimaran et al, 2016). It has also been reported that the most common uterine disease is metritis in dairy cows (Kurt et al, 2019), with an approximately 20% incidence (Pérez-Báez et al, 2021). Moreover, uterine diseases can occur in the form of endometritis or metritis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastitis in cows is categorized as a subclinical and clinical inflammatory disease of the mammary gland caused by a variety of stimulating factors, such as pathogens, physical and chemical factors and mechanical stimulus. It negatively affects animal welfare, milk quality, farmer serenity, and farming profitability and causes substantial economic losses throughout the world ( 1 , 2 ). Previous researches have included investigation into the prevention and treatment of cow mastitis, such as vaccine development ( 2 , 3 ), discovery of new drugs and new approaches of treatment ( 4 ), and exploring the veterinary medicinal compounds and monomer extracts of traditional Chinese medicine ( 5 ).…”
Section: Introductionmentioning
confidence: 99%